Hamito-Semitic etymological dictionary : materials for a reconstruction - Orel, Vladimir E. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1995)
The Hamito-Semitic Etymological Dictionary , a project in the making since 1986, is the first dictionary to reflect the vocabulary of the extinct Proto-Hamito-Semitic (Proto-Afro-Asiatic) language. Reconstructed on the basis of Semitic, Ancient Egyptian, Berber, Chadic and Cushitic linguistic groups, the Dictionary plays an indispensable role in further research into the field of historical linguistics. It surpasses by far the only comparable work to date, M. Cohen's Essai comparatif sur le vocabulaire et la phonetique du chamito-semitique , published in 1947, which contains much less material and is now outdated. The Dictionary comprises more than 2,500 lexical items and includes an introduction providing valuable information on the historical phonology of Hamito-Semitic as well as an index of meanings, which supplies linguistics, archaeologists and scholars of ancient history with added insight into the culture of the ancient speakers of Proto-Hamito-Semitic. An invaluable contribution to the field of Afro-Asiatic Studies, The Hamito-Semitic Etymological Dictionary will be used and discussed by scholars for years to come.